PENGARUH IMPOR BERAS TERHADAP KETAHANAN PANGAN INDONESIA THE EFFECT OF RICE IMPORTS ON INDONESIA’S FOOD SECURITY - Rahman, Irvan Unzia; Damayanti, Christy; Dipokusumo, GPH (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2020)
This research explains and analyzes the importance of imports on Indonesia's food security. This research was examined using the theory of rice import and the concept of food security. This research aims to study how important rice is for Indonesia's food security. This research method uses qualitative descriptive methods and quantitative data as supporting material with secondary data collection. This data collection is based on a descriptive translation document and online media. From the analysis conducted, the researchers found that important rice activities had a major influence on Indonesia's food security. Indonesia's policy needs to be imported to stock up on rice reserves and fixed prices as well as the population growth. Indonesia's food security will still be possible if enough food is provided to the State and society. Keywords: Rice, Rice Import, Indonesian Food Security